(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Walking considered as one of the safest modes of travel available, sustainable to human society as well as environmentally beneficial. In this context, the aim of this research is to investigate pedestrians’ traffic gap acceptance and crossing decision for Mid-block Street crossing in urban areas in Malaysia. Pedestrian crossing behaviour at Rughaya Street has been examined in terms of the decision to cross or not the street and size of traffic gaps accepted by pedestrian, as well as the related contributing factors. A field study was conducted to collect the data of pedestrians’ decisions under real mix traffic Condition using video camera on a typical unsignalized urban street section. JPEG files were obtained from video recording by using Snapshot Wizard software. The data extracted included traffic characteristics such as traffic size, traffic speed, etc. pedestrian individual characteristics such as gender, in addition to individual behavior such as waiting, frequency of attempt, etc.). Furthermore, The extracted data were used to develop and examine a pedestrian gap acceptance model based on A lognormal regression model and binary logistic model by SPSS (22) in order to validate the impact of various parameters on the size of traffic gaps accepted by pedestrians as well as the effect on the decision of pedestrians to cross the street or not.